IMPLEMENTASI MEDIA PERMAINAN CODAKA DALAM MENINGKATKAN HASIL BELAJAR RANAH KETERAMPILAN SISWA DI KELAS IV SDN SAMBUNG - Lestari, Endang Eni; Roysa, Mila; Purbasari, Imaniar (Universitas Sarjanawiyata Tamansiswa, 2020)
This study aims to describe the improvement of the learning outcomes of the students in the fourth grade of SDN Sambung using Codaka game media. This research is a classroom action research. The research subjects were 23 grade IV students of SDN Sambung. Data collection techniques obtained from observation, documentation, and tests. Data analysis techniques using quantitative and qualitative data analysis. The results of the implementation of Codaka game media in class IV SDN Sambung obtained that the observed student skills included listening, communication, and participation skills. The listening skills of the first cycle students, the percentage of students who completed was 65% and increased in the second cycle to 83%. In the first cycle communication skills, students who completed obtained a percentage of 57% while the second cycle gained 78%. Cycle participation skills, the percentage of students who completed was 65% while in cycle II the percentage was 83%. Based on these data it can be concluded that listening skills, communication, and student participation in cycle I to cycle II have increased so that they can reach the percentage of completeness of more than 75% so that it can be concluded that the media of Codaka games can improve student learning outcomes in the realm of skills.